I Hear You: Constructing Common Knowledge Practices in the Context of Organizational Meetings - Mariano, Stefania (2021)
Purpose: The purpose of this study is to provide a granular description of how organizational members construct common knowledge practices in the context of organizational meetings. Design/methodology/approach: A longitudinal interpretative case study methodology was used to collect data from a US-based organization involved in an information system implementation project. Findings: Findings revealed that during meetings common knowledge was constructed through four practices of discernment, compliance, reconstruction and expedition. Findings also revealed that these four practices were influenced by intervening conditions such as calibration challenges and scenario-sharing tools. Research limitations/implications: The findings of this study have research implications related to common knowledge construction and co-participation practices in the context of organizational meetings. This study has limitations related to statistical generalizability that have been mitigated through a holistic approach to case study methodology that favors analytical generalizability of research findings. Practical implications: This study provides managers with recommendations that suggest a more strategic use of meetings as useful organizational contexts that may help construct common knowledge practices and shared understanding. Originality/value: This study contributes to current theorizations of common knowledge by providing an in-depth understanding of the construction of common knowledge practices in organizations. This study also sheds some light on the strategic role of organizational meetings to manage knowledge in project-based organizational contexts.